DEVELOPING A GUIDEBOOK OF BRIDGE POSITIONS FOR GRADE IV-VI STUDENTS’ SPORTS EDUCATION - Ikari, Steven David (Interdisciplinary Social Studies, 2022)
Background: The bridge position is contained in the material book in school and joined by other materials such as large balls, small balls, and so on, which is the advantage of this rich guidebook is that it can be used anywhere and has barcodes to access bridge position training tutorial videos. With this guidebook, learners can do bridge position activities independently and also teachers have additional material resources to train bridge position on learners. Aim: This research aims to give more insight into the development of guidebooks for sports and health education for students, especially those who are in the 4th-6th grade of elementary school. Method: The research method used in this research is Research and Development (R&D). The product developed by the researchers is a guidebook with the title "Bridge position Method Guide For Class IV-VI". The guidebook of bridge position method was developed by researchers using expert judgment, then processed to get perfect results. Findings: Based on the results of the data analysis obtained from expert validation tests with excellent criteria, it can be stated that the guidebook product of grade IV-VI elementary school is a valid product and can be used as one of the learning resources for learners.